PENGARUH PENYULUHAN PERTANIAN DALAM ASPEK LINGKUNGAN, EKONOMI DAN TEKNOLOGI PADA PETANI PADI SAWAHDI KECAMATAN MODAYAG - Sopiyan ., Hasan; Wenny ., Tilaar; Lientje Theffie Karamoy (AGRI-SOSIOEKONOMI, 2016)
The purpose of this study was to analyze whether the Environmental Aspects influencing on rice production in Sub-district of Modayag, to analyze whether the Economics aspect affect on of rice production in Sub-district Modayag and to analyze whether the effect of the technology aspects on rice production in Sub-district of Modayag. The research was conducted on a group of Paddy Rice Farmers in the Sub-district of Modayag, East Mongondow Bolaang District, in March 2015 until December 2016. The colection of primary data conducted after the agricultural extension officer held the extension in January 2016. The study lasted approximately 1 year to examine the changes in the knowledge, skills and attitudes of paddy rice farmers. Retrieving data using questionnaires to 30 (thirty) of respondents from Rice farmers in Sub-district of Modayag. From this study it can be concluded that the extension of an underlying process on Environmental Aspects, Economics and Technology Aspects effect on changes in knowledge, skills and attitudes of paddy farmers in the Sub-district of Modayag. The third aspect of the existing namely Environmental Aspects, Economics and Technology Aspects of the most influential in the process of agricultural extension is Economics.